Corporate criminal liability: similarities and differences between Spain and Philippines - Fernández-Díaz, Carmen Rocío (My University, 2018)
This paper focuses on the topic of corporate criminal liability and the common and opposite aspects that regimes of Spain and The Philippines have. On the one hand, in Spain, criminal liability of legal persons has suffered a deep reform with the organic law 1/2015, after being introduced in year 2010. This reform has brought important modifications and news, as the creation of an exemption of liability through the adoption of compliance programs. On the other hand, corporate criminal liability is more limited in The Philippines, being criticized by the doctrine that, rather to impose this kind of liability to companies, natural persons as directors, officers or employees of the corporation are the only ones considered responsible for some crimes. The analysis of both regimes, the Spanish and the Philippines one, will comprise different aspects of the issue as the crimes for which companies can be criminally liable, the ways to require to them criminal liability or their exemption of it and the possible sanctions that can be imposed. The comparative study will bring out the positive and the negative points of both regimes.
Keywords: Derecho penal; Corporate; Criminal liability; Criminal law; Spain; Philippines